TINJAUAN YURIDIS PENERAPAN UNDANG-UNDANG NO.11 TAHUN 2012 TENTANG SISTEM PERADILAN ANAK, TERHADAP SANKSI PIDANA ANAK SEBAGAI PELAKU TINDAK PIDANA NARKOTIKA (STUDI KASUS PADA WILAYAH HUKUM PENGADILAN NEGERI LUBUK PAKAM No. 10/PID/SUS-Anak/2017/PN-LBP ) - ERNAWATI BR BARUS (Ilmu Hukum Prima (IHP), 2021)
The child is a treasure God Almighty that is highly anticipated by a family, because aside from being a descendant of a family of children as well as the next generation of the nation and successor development, namely a generation that is prepared as a subject of implementing sustainable development and control the future of a country. As time goes by children not only as a victim in a crime but there have been many children involved as perpetrators of the crime, in this case was the crime of narcotics is one of the extraordinary crime or "extraordinary crime". Regulations governing the criminal justice system of children aims to protect the rights of the child. Based on the background, the author raised the Thesis entitled "Juridical Review the implementation of the law No. 11 Year 2012 On Child justice system, criminal sanctions against children as perpetrators of Crime Narcotics (case study on Pengadilam of State jurisdiction Lubukpakam No. 14/Pid. Child/Sus-2017/PN-LBP, no. 15/Pid. Sus-child/2017/PN-LBP and no. 32/Pid. Sus-child/2017/PN-LBPMetode research in this thesis is done with normative juridical research is to do an analysis of the problem through legal principles as well as referring to the legal norms contained in the legislation. The data used are sourced from primary and secondary legal materials through the library reseach using research data from a variety of sources such as legislation, reading books, and the internet are judged relevant to this thesis was elevated to discover sejauhmana the application of law number 11 Year 2012 against the perpetrators of the crime of narcotics on the State Court jurisdiction Lubukpakam.